The Effect of the Combination of Semi Fowler Position and Pursed Lip Breathing Technique on Increasing Oxygen Saturation in COPD Patients in the ER Room at Dr. M.M. Dunda Limboto Hospital - Lutfi Alfadel Razak; Ita Sulistiani; Ibrahim Suleman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Chronic Obstructive Pulmonary Disease (COPD) is one of the lung diseases characterized by chronic and progressive limited airflow due to obstructions in the airways. This condition causes gas exchange disorders that cause shortness of breath, coughing up phlegm, wheezing, and fatigue due to damage to lung tissue or blockage by phlegm. This study aims to find out whether there is an effect of the combination of semi fowler position and purse lip breathing technique on increasing oxygen saturation in COPD patients. The type of Quasi Experiment research is through a pretest-posttest design control group approach. The population in this study was patients diagnosed with chronic obstructive pulmonary disease (COPD) in the emergency room of Dr. M.M. Dunda Limboto Hospital as many as 70 patients., with sampling techniques using Accidental Sampling amounting to 42 then divided into 21 Intervention groups and 21 Control groups. The level of combination of semi fowler position and Purse Lip Breathing technique, Data analysis was carried out using the Paired Samples T-test. The results showed that in the intervention group, there was a significant increase in oxygen saturation after the intervention, with a value of sig (2-tailed) = 0.000 (<0.05), so that H0 was rejected and Ha was accepted. Similarly, in the control group, the increase in oxygen saturation was also significant with the value of sig (2-tailed) = 0.000 (<0.05). These findings show that the combination of the Semi Fowler position and the Pursed-Lip Breathing technique effectively increases oxygen saturation in COPD patients in the ER. The conclusion of this study is that there is an effect of the combination of the Semi Fowler position and the Pursed-Lip Breathing technique and is proven to be effective in increasing oxygen saturation in COPD patients in the ER, so that this intervention can be used as a recommended non-pharmacological strategy in the treatment of COPD patients.